2016
DOI: 10.1111/apt.13889
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is associated with severe liver fibrosis in patients with non-alcoholic fatty liver disease

Abstract: In Western patients with NAFLD, with high prevalence of metabolic disorders and advanced liver disease, sarcopenia was associated with the severity of fibrosis and steatosis, independently of hepatic and metabolic risk factors. Studies are needed to assess the impact of interventions to reduce sarcopenia on NAFLD progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(183 citation statements)
references
References 42 publications
11
162
10
Order By: Relevance
“…(34) In a sample of Caucasians, a significant association was found between sarcopenia estimated by BIA and severe steatosis defined by liver biopsy (adjusted odds ratio = 2.02, 95% CI = 1.06-3.83). (22) Lee et al (11) reported that sarcopenia was associated with a 1.18-fold increased prevalence of NAFLD defined by HSI score independent of obesity and insulin resistance. Consistent with these results, the present 7-year longitudinal study confirmed these findings and suggested a causal link in a large sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(34) In a sample of Caucasians, a significant association was found between sarcopenia estimated by BIA and severe steatosis defined by liver biopsy (adjusted odds ratio = 2.02, 95% CI = 1.06-3.83). (22) Lee et al (11) reported that sarcopenia was associated with a 1.18-fold increased prevalence of NAFLD defined by HSI score independent of obesity and insulin resistance. Consistent with these results, the present 7-year longitudinal study confirmed these findings and suggested a causal link in a large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The BIA technique was validated for the assessment of body composition, showing good correlation with dual-energy x-ray absorptiometry, and applied to estimate ASM in several recent studies. (19)(20)(21)(22)(23) The skeletal muscle mass index (SMI) was calculated by dividing the sum of the ASM in the bilateral upper and lower four limbs (kg) by body weight (kg) and expressed as a percentage (= total ASM/body weight × 100%) as a modified formula from the study of Janssen et al (11,(23)(24)(25)(26) Change in SMI over the course of 1 year from baseline was calculated by subtracting baseline SMI from SMI at the 1-year follow-up visit. Also, change in SMI over a longer time was defined by subtracting baseline SMI from SMI at the follow-up visit.…”
Section: Measurement Of Appendicular Skeletal Muscle Mass and Definitmentioning
confidence: 99%
“…Thus far, there are only two studies looking at the association between sarcopenia and NAFLD in non-Asian populations. (50,51) An Italian study showed that sarcopenia was associated with both visceral obesity and IR. (50) This study also showed an increase in the prevalence of sarcopenia with worsening fibrosis, independent of obesity and IR.…”
Section: Impact Of Sarcopenia In Nashmentioning
confidence: 99%
“…Several reports showing that the proportion of decreased skeletal muscle mass (D-SMI) demonstrated a linear increment with liver fibrosis progression in non-alcoholic fatty liver disease (NAFLD) or non-alcoholic steatohepatitis (NASH) patients support our hypothesis [33,34,35]. However, an extensive literature search has not shown the relationship between skeletal muscle mass and the liver fibrosis markers in CLD patients, and these clinical questions should be fully addressed.…”
Section: Introductionmentioning
confidence: 60%